Evaluating Customer Relationship Management Scorecard with Special Reference to Vellore District - Sasikala D; Vasantha S; Sangeetha M (International Journal of Supply Chain Management, 2018)
The activities of the banking industry are diverse and competitive. There is a paradigm shift in banking business involving a network of the financial transaction to manage all aspects of a customer's financial portfolio. Banks today face complex challenges and multiple threats to its existence and growth. Customer expectations are growing with the demand for more rapid service delivery and more flexible, personalized interaction. The wave of liberalization, privatization, and globalization of the Indian economy has given a lot of challenges to this sector. A small attempt has been made in the marketing of financial services with the help of customer relationship management scorecard and brand perception metrics scorecard. Keywords: customer relationship management, scorecard, Brand perception metrics scorecard, Balance scorecard, SERVQUAL